Home cooked : 100 essential recipes for a new way to cook - Fernald, Anya; Battilana, Jessica (Ten Speed Press, 2016)
"A recipe collection and how-to guide for preparing base ingredients that can be used to make simple, weeknight meals, while also teaching skills like building and cooking over a fire, and preserving meat and produce, written by a sustainable food expert and founder of Belcampo Meat Co. Anya Fernald's style of cooking is rustic and simple, shaped by her years working on farms, living in Italy, and running Slow Food Nation--but it's also sophisticated and brilliant. Her secret is that by taking the time to create beautiful, super-flavorful base ingredients ahead of time--such as homemade sauces, preserves, pickles, and cured meats--you can easily create fast but luscious meals later using these components. InHome Cooked, Fernald teaches readers her methods and heritage skills to help them become more intuitive, natural home cooks who don't need to rely on recipes. Along the way, she shares kitchen tips and tricks for transforming food into something truly special, as well as her food philosophy and inspired approach to home cooking"--